2017
DOI: 10.1055/s-0037-1607214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ulnar Styloid Fractures on Unstable Distal Radius Fracture Outcomes: A Systematic Review of Comparative Studies

Abstract: In this literature review, functional outcomes such as Disability of Arm, Shoulder and Hand (DASH) score and the visual analog scale (VAS) of pain along with clinical outcomes such as range of movement and grip strength of treated distal radius fractures (DRF) accompanied with ulnar styloid fractures (USF) will be compared with those with isolated DRF. We analyzed articles from MEDLINE, Embase, and CINAHL that met our predetermined inclusion and exclusion criteria as per the Preferred Reporting Items for Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Previous biomechanical studies have indicated that the middle column of the distal radius is the hub and primary load-bearing surface, which transmits an axial load to the wrist and has a major role in mechanical conduction (10). The fracture line of the middle column of the distal radius is usually vertical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous biomechanical studies have indicated that the middle column of the distal radius is the hub and primary load-bearing surface, which transmits an axial load to the wrist and has a major role in mechanical conduction (10). The fracture line of the middle column of the distal radius is usually vertical.…”
Section: Discussionmentioning
confidence: 99%
“…The Melone and Fernandez classification systems have been extensively cited by previous studies (17)(18)(19)(20)(21). Although this type of double-column die-punch fracture is widely known, the description of double-column die-punch fractures of the distal radius has not been previously reported (10,22). Therefore, a lack of studies is available regarding the mechanism of the occurrence and classification of double-column die-punch fractures.…”
Section: Discussionmentioning
confidence: 99%
“…An accompanying ulnar styloid fracture in patients with stable fixation of a distal radial fracture had no apparent adverse effect on wrist function or stability of the distal radioulnar joint . The recent meta‐analyses also showed that no significant difference was found in wrist scores, range of motion, grip strength, pain scores and distal radioulnar joint instability between patients with and without an ulnar styloid process fracture after 1 year of follow‐up …”
Section: Discussionmentioning
confidence: 97%
“…A recent meta-analysis revealed functional scores favoring distal radius fractures without concomitant ulnar styloid fractures while the outcome difference was not significant in patients with and without ulnar styloid fractures [ 14 ]. In literature review, most of those studies anecdotally evaluated ulnar styloid fractures based on the outcomes of concomitant distal radius fractures and commonly introduced bias assuming more complicated presentation in surgical treated ulnar styloid fractures than non-surgical cases to reach a conclusion of no significant difference [ 15 ]. Besides, surgical concerns existed almost uniquely in styloid base fractures owing to both fixation feasibility [ 7 ] and cadaveric demonstration [ 16 ].…”
Section: Discussionmentioning
confidence: 99%